High Watermarking Image Quality Based on Dual Intermediate Significant Bit (DISB) - Mohammed, G; Yasin, A; Zeki, Akram M. (AICIT, 2013)
The most important requirement of any watermarking system is the quality of the watermarked images. In most applications, the watermarking algorithm embeds the watermark without affecting the quality of the host media. In this study, the method focuses on the watermarked image of the high quality based on Dual Intermediate Significant Bit (DISB) model. This method requires embedding two bits into every pixel of the original image, while and the other six bits are changed so as to directly assimilate the original pixel. In the case, when the two hidden bits are equal to the original bits, there will be no change to the other remaining bits. However, if the original value is not equal to the embedded one, the nearest pixel to the original will be chosen as the watermarked image. The results show that the proposed model produces high quality watermarked image as compared to the quality of the watermarked image produced by the use of Least Significant Bit (LSB) method.